2020
DOI: 10.2174/1573401315666191003153807
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Acceptability of Chin-chin Prepared from Rice and High Quality Cassava Composite Flour

Abstract: Objective: This study was carried to assess the quality characteristics and acceptability of chin-chin prepared from rice and high-quality cassava composite flour. Methods: Chin-chin samples were made from the blends of rice flour (RF) and high quality cassava composite flour (HQCF) at varying proportions (100:0; 90:10; 80:20; 70:30; 60:40; 50:50; 0:100). The proximate composition, calorific and total energy values, physical quality, crust colour and the sensory properties of various chin-chin samples were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…T2 (20% rice) had the greatest average loaf volume (437.33±67.29 ml) which was similar (p>0.05) to the control (384.40±54.58 ml) and significantly higher (p≤0.05) than T3 (98.27±17.26 ml) and T4 (28.23±13.42 ml) bread samples. [24] and [21] also found that as the level of rice flour incorporation increased there was a decrease in loaf volume. The loaf volume of bread produced from other types of composite flours such as sesame-wheat, maize-sweet-potato-wheat, and oil beanwheat were significantly lower than the control treatments (100% wheat), and loaf volume significantly decreased as the level of sesame, maize-sweet potato, and oil bean flour increased [22], [16], [23].…”
Section: B Physical Properties Of Breadmentioning
confidence: 91%
See 3 more Smart Citations
“…T2 (20% rice) had the greatest average loaf volume (437.33±67.29 ml) which was similar (p>0.05) to the control (384.40±54.58 ml) and significantly higher (p≤0.05) than T3 (98.27±17.26 ml) and T4 (28.23±13.42 ml) bread samples. [24] and [21] also found that as the level of rice flour incorporation increased there was a decrease in loaf volume. The loaf volume of bread produced from other types of composite flours such as sesame-wheat, maize-sweet-potato-wheat, and oil beanwheat were significantly lower than the control treatments (100% wheat), and loaf volume significantly decreased as the level of sesame, maize-sweet potato, and oil bean flour increased [22], [16], [23].…”
Section: B Physical Properties Of Breadmentioning
confidence: 91%
“…According to [21], loaf weight is determined by the amount of dough baked and the amount of moisture and carbon dioxide released from the loaf during baking. Since rice flour is non-glutenous, it aids in moisture and carbon dioxide loss in the loaf which reduces both weight and volume of the bread [21].…”
Section: B Physical Properties Of Breadmentioning
confidence: 99%
See 2 more Smart Citations
“…For many years, now, bread has been a major staple wheat-based food product with rapid increasing consumption worldwide, especially, in Nigeria and other developing countries (Adeyeye et al, 2019;Akubor and Gambo, 2020;Wang and Jian, 2022;Moreno-Araiza et al, 2023). It is prepared from hard wheat flour, yeast, fat, sugar, salt and water.…”
Section: Introductionmentioning
confidence: 99%